Jurnal Akuntansi & Investasi:Pengaruh Return on Asset, Ukuran Perusahaan dan Financial Leverage terhadap Tindakan Perataan Laba (Studi Empiris Pada Perusahaan Sektor Keuangan yang Terdaftar di BEI) - MS Kurniawan, Sri Wahjuni Latifah, Siti Zubaidah (Akuntansi FE UMY, 2012)
The aimed of this study was to examine the influence of companys characterictics toward income smoothing practice among listed companies at Indonesian Stock Exchange. The factors being examined were return on asset, company size and financial leverage. Index Eckel is used to determine the income smoothing practice. The study was using 43 finance companies listed at Indonesian Stock Exchange, with a period between 2006-2010